Evaluation of physical-chemical and microbiological characteristics of freeze-dried and reydrated yogurt (Research, Society and Development, 2020)
This study aimed to evaluate the physical-chemical characteristics and the viability of lactic acid bacteria during the fermentation process of the yogurt and after the freeze-dried process, in addition to testing three thickener formulations for the rehydration of the yogurt powder. During the fermentation process, the production of lactic acid and the growth of lactic acid bacteria were accompanied.  Before and after freeze-dried process, yogurt was analyzed for pH, titratable acidity, carbohydrates, proteins, lipids and viable lactic acid bacteria. After lyophilization, three thickener formulations were tested to evaluate the rehydration of powdered yogurt. At the end of the fermentation process, it was verified that the lactic acid bacteria grew to reach 7.8.107 UFC.g-1 and the acidity obtained was 9.27 g.L-1.  The viable lactic acid bacteria count of freeze-dried and non-freeze-dried yogurt was 5.6.107 CFU.g-1 and 7.8.107 CFU.g-1, respectively. Non-freeze-dried and freeze-dried yogurts showed a content of 20.8% and 21.0% carbohydrates, 4.0% and 3.6% protein and 3.7% and 2.7% lipids, respectively. The combination of thickeners that provided viscosity similar to commercial yogurts was the guar gum, pectin and maltodextrin mix. Thus, it was possible to verify that the freeze-drying process maintains the physical-chemical characteristics and viability of lactic acid bacteria. In addition, the developed yogurt presented easy reconstitution at the time of consumption.